-12x=-15x+-36

Simple and best practice solution for -12x=-15x+-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x=-15x+-36 equation:



-12x=-15x+-36
We move all terms to the left:
-12x-(-15x+-36)=0
We add all the numbers together, and all the variables
-12x-(-15x-36)=0
We get rid of parentheses
-12x+15x+36=0
We add all the numbers together, and all the variables
3x+36=0
We move all terms containing x to the left, all other terms to the right
3x=-36
x=-36/3
x=-12

You can always share this solution

See similar equations:

| (Z=4)19-2z | | 2x+7x+x=180° | | 8n^2+8n-576=0 | | 4x+21+4x=3x-14 | | -(-9x+1)=10 | | -2x-2=34 | | 7y+2=5y+26 | | V=12x11/3 | | -y+12-2y=2 | | -5x+23=13 | | 8.6=2.1?1.3y | | 3x-3=-84 | | 6-4•n=12 | | x-4-3x=10-6 | | -x/5+4=13 | | -13.5/x=-2.50 | | 8^x=2x+2 | | 2x-6=4x-36 | | 42÷m=7 | | y+-13=-8 | | 5y-(-17)=33 | | 2x+5=12x*10 | | –2s+–9=–1 | | S=t2+4 | | 7x+50=80x | | 15x–12=8+10x | | 4–x=3x+6 | | (9x-7)=(-3x-4) | | -2/3x+2=-11 | | 7x+50=10x | | -3(n-5)=30-3n | | 5x+6=-5 |

Equations solver categories